Axonal α-synuclein aggregates herald centripetal degeneration of cardiac sympathetic nerve in Parkinson's disease - Orimo, Satoshi; Uchihara, Toshiki; Nakamura, Ayako; Mori, Fumiaki; Kakita, Akiyoshi; Wakabayashi, Koichi; Takahashi, Hitoshi (Brain (London, England : 1878), 2008)
Degeneration of the cardiac sympathetic nerve occurs in both Parkinson's disease (PD) and dementia with Lewy bodies and begins early in the disease progression of PD, accounting for reduced cardiac uptake of meta-iodobenzylguanidine even in the early stages of Lewy body disease (LBD). We previously demonstrated that degeneration of the distal axons of the cardiac sympathetic nerve precedes loss of their mother neurons in the paravertebral sympathetic ganglia, suggesting distal dominant degeneration of the cardiac sympathetic nerve in PD. Because α-synuclein is one of the key molecules in the pathogenesis of this disease, we further investigated how α-synuclein aggregates are involved in this distal-dominant degeneration. Both cardiac tissues and paravertebral sympathetic ganglia were obtained for comparison from 20 patients with incidental Lewy body disease (ILBD), 10 with PD, 20 with multiple system atrophy (MSA) and 10 control subjects. Immunohistochemical analysis was performed using antibodies against tyrosine hydroxylase (TH) as a marker for sympathetic nerves, phosphorylated neurofilament as a marker for axons and phosphorylated α-synuclein for pathological deposits. We found that (i) α-synuclein aggregates in the epicardial nerve fascicles, namely the distal axons of the cardiac sympathetic nerve, were much more abundant in ILBD with preserved TH-ir axons than in this disease with decreased TH-ir axons and PD; (ii) α-synuclein aggregates in the epicardial nerve fascicles were closely related to the disappearance of TH-ir axons; (iii) in ILBD with preserved TH-ir axons, α-synuclein aggregates were consistently more abundant in the epicardial nerve fascicles than in the paravertebral sympathetic ganglia; (iv) this distal-dominant accumulation of α-synuclein aggregates was reversed in ILBD with decreased TH-ir axons and PD, which both showed fewer of these axons but more abundant α-synuclein aggregates in the paravertebral sympathetic ganglia and (v) MSA was completely different from ILBD and PD based on the preservation of TH-ir axons and the scarcity of α-synuclein aggregates in either the cardiac tissues or the paravertebral sympathetic ganglia. These findings indicate that accumulation of α-synuclein aggregates in the distal axons of the cardiac sympathetic nervous system precedes that of neuronal somata or neurites in the paravertebral sympathetic ganglia and that heralds centripetal degeneration of the cardiac sympathetic nerve in PD, which sharply contrasts with slight changes in MSA. This chronological and dynamic relationship between α-synuclein aggregates and distal-dominant degeneration of the cardiac sympathetic nervous system may represent the pathological mechanism underlying a common degenerative process in PD.